Academic Personnel System Reforms in China: Trajectory and Tensions - Li, Qi (International Higher Education, 2024)
While the past four decades of academic personnel system reforms have changed the relationship between faculty and their institutions and boosted the competitiveness of China’s higher education in the international arena, further reforms or change will be required to reduce tensions and achieve a sustainable future.